Dedi Mulyadi's Populism in Building Political Communication Through Social Media Content - Alfin Aldiansyah; Muhammad Ruslan Ramli (Riviera Publishing, 2026)
This research discusses the populism displayed by KDM or Dedi Mulyadi through social media TikTok, as well as how the public responds to it. KDM actively uses social media as a way to build personal branding. The problem is how the form of populism displayed by Dedi Mulyadi in Tiktok content, and how the public responds to it. The goal is to explain the form of populism used on TikTok's social media, and the public's response to it. This study uses the Populism Theory from Cas Mudde and Rovira Kaltwasser and the Reception Theory from Stuart Hall, with the method of Critical Discourse Analysis or AWK. The paradigm uses constructivism with critical discourse analysis techniques. The analysis focuses on four category clusters, namely Politics, Social, and Family. Analysis was carried out on Dedi Mulyadi's content in one period, and interviews were conducted with people from various backgrounds. The results found that Dedi Mulyadi adheres to moralistic, cultural, and personal populism, namely populism. who consciously build personal and moral closeness. Then it was also found that three of the six speakers with a percentage of fifty percent chose to be in the Negotiated position or agreed with several notes on the way carried out by Dedi Mulyadi.